The Wright brothers - McCullough, David G. (New York : Simon & Schuster, 2015)
On a winter day in 1903, in the Outer Banks of North Carolina, two unknown brothers from Ohio changed history. But it would take the world some time to believe what had happened: the age of flight had begun, with the first heavier-than-air, powered machine carrying a pilot. Who were these men and how was it that they achieved what they did? Far more than a couple of unschooled Dayton bicycle mechanics who happened to hit on success, they were men of exceptional courage and determination, and of far-ranging intellectual interests and ceaseless curiosity, much of which they attributed to their upbringing. The house they lived in had no electricity or indoor plumbing, but there were books aplenty, supplied mainly by their preacher father, and they never stopped reading. When they worked together, no problem seemed to be insurmountable. Wilbur was unquestionably a genius. Orville had such mechanical ingenuity as few had ever seen. That they had no more than a public high school education, little money and no contacts in high places, never stopped them in their mission to take to the air. Nothing did, not even the self-evident reality that every time they took off in one of their contrivances, they risked being killed. Historian David McCullough draws on the immense riches of the Wright Papers, including private diaries, notebooks, scrapbooks, and more than a thousand letters from private family correspondence to tell the human side of the Wright Brothers' story, including the little-known contributions of their sister, Katharine, without whom things might well have gone differently for them
Beginnings -- The dream takes hold -- Where the winds blow -- Unyielding resolve -- December 17, 1903 -- Out at Huffman prairie -- A capital exhibit A -- Triumph at Le Mans -- The crash -- A time like no other -- Causes for celebration.
Includes bibliographical references (pages 269-308) and index.
Keywords: Wright, Orville, -- 1871-1948.; Wright, Wilbur, -- 1867-1912.; Aeronautics -- United States -- History -- 20th century; Flight -- United States -- History -- 20th century; Biographies